2014
DOI: 10.1016/j.foodcont.2013.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Conducting inferential statistics for low microbial counts in foods using the Poisson-gamma regression

Abstract: Mixed Poisson distributions have been shown to be able to represent low microbial counts more efficiently than the lognormal distribution because of its greater flexibility to model microbial clustering even when data consist of a large proportion of zero counts. The objective of this study was to develop an alternative modelling framework for low microbial counts based on heterogeneous Poisson regressions. As an illustration, Poisson-gamma regression models were used to assess the effect of chilling on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…These regression models have been recently adopted to analyze microbial count data taking into other covariates into account. [30, 31] In addition, we performed principal component analyses at class, family and species levels where relative abundance of each bacterial group was square root transformed as it performed better than other transformations, such as natural log or arcsine. Analysis of variance was used to compare principal component scores as well as UniFrac distances of principal coordinates between subject groups with adjustment for selected covariates where first coordinate distances were natural log-transformed to improve deviation from normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…These regression models have been recently adopted to analyze microbial count data taking into other covariates into account. [30, 31] In addition, we performed principal component analyses at class, family and species levels where relative abundance of each bacterial group was square root transformed as it performed better than other transformations, such as natural log or arcsine. Analysis of variance was used to compare principal component scores as well as UniFrac distances of principal coordinates between subject groups with adjustment for selected covariates where first coordinate distances were natural log-transformed to improve deviation from normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…As the untransformed L. monocytogenes data (CFU/g) was overdispersed (variance ≫ mean), consisting of low microbial counts and large proportion of zero counts (non-detections), a Poisson-gamma (negative binomial) count data model was opted for. Earlier, Gonzales- Barron, Cadavez, and Butler (2014) demonstrated that this type of count data models along with their zero-modified counterparts are much more suitable for inferential assessment than normality-based regression models when analysing over-dispersed microbiological data. Thus, in order to appraise the same fixed effects as in Eqs.…”
Section: Analysis I: Associations Between Physicochemical Properties and Microbial Counts Along Processingmentioning
confidence: 99%
“…In preharvest practice, a hurdle model can be considered the most optimal modeling choice because modeling predictions can be directly compared and verified against observations. Nevertheless, only a small number of previous studies have applied this model in the food safety field, such as on samples from beef carcasses (24,54). To our knowledge, there are no other studies that investigated risk factors of produce contamination with a microorganism using a hurdle model.…”
Section: Discussionmentioning
confidence: 99%